ACCIDENTS AND INJURIES IN RURAL AREAS OF NORTHWEST OF IRAN - M.R. Attari-Barough; A. Nadim (Tehran University of Medical Sciences, 1997)
A study has been carried out in 1992 to determine the incidence mortality and disability due to accidents and injuries in more than seven hundred thousand population under the coverage of Health Houses in East Azerbaijan province, northwest of Iran. This study showed that burns, falls, road accidents and those related to agricultural and other equipments are the main types of accidents. Road accidents, burns suicides and suffocations were the main causes of accident deaths. Both the types and the end-results of accidents were different in various age groups and between male and female. Recommendations are presented for further studies and for reducing the health burden of these problems.